Oil spill extraction from X-band marine radar images by power fitting of radar echoes. Issue 4 (3rd April 2021) - Liu, Peng; Zhao, Yancheng; Liu, Bingxin; Li, Ying; Chen, Peng
ABSTRACT: Oil spills cause great environmental damage and the ability to identify them accurately is important to prompt oil spill response. A power fitting method of radar echo is proposed in this paper to detect oil spills on sampled X-band marine radar images. In this method, first, the marine radar image is pre-processed, including coordinate transform and noise reduction. Then, the difference between the pre-processed radar image and power fitting result is obtained. Finally, oil spills are extracted by using a mean filter, the Otsu method, and connected component analysis. The proposed oil spill detection method was used on radar images sampled after an oil spill accident in the coastal region of Dalian, China, on 21 July 2010. The proposed method can detect oil spills without manual participation, and the extracted oil spills are comparable to visual interpretation.